Effects of nanoimprinted patterns in tissue-culture polystyrene on cell behavior - Hu, W; Yim, E K F; Reano, R M; Leong, K W; Pang, S W (Journal of vacuum science & technology. A, Vacuum, surfaces, and films, 2005)
Tissue engineering seeks to develop functional tissues in a biomimetic environment in vitro. As the extracellular environment in vivo is composed of numerous nanostructures, fabrication of nanostructured substrates will be valuable for tissue engineering applications. In this article, we report a simple nanoimprint lithography (NIL) process to pattern nanostructures directly on tissue-culture polystyrene plates. By repeating this NIL process, three-dimensional scaffolds consisting of multiple-layer nanostructures were also fabricated. Bovine pulmonary artery smooth muscle cells were cultured on imprinted gratings ranging from 350 nm to 10 μm. The smooth muscle cells attached and proliferated well on these imprinted substrates without additional surface treatment. Cell elongation and alignment were observed on the micro- and nanopatterns, with the effect significantly more pronounced on the nanostructures.